Practitioner’s field guide: agroforestry for climate resilience - Martini, E.; Nguyen, H.T.; Mercado Jr, A.R.; Finlayson, R.; Nguyen, Q.T.; Catacutan, D.C.; Triraganon, R. (World Agroforestry Centre, 2021)
Climate change is increasingly experienced in Southeast Asia in the form of rising temperatures, longer periods of hot weather, prolonged droughts, more powerful typhoons, and extreme rainfall. Farmers in many parts of the region are facing degradation of arable land, shortage of water, increased occurrence of pests and diseases, declines in crop and livestock productivity and loss of yields. Consequently, their income and food security has been severely threatened.